2018
DOI: 10.1126/science.aan3706
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome influences efficacy of PD-1–based immunotherapy against epithelial tumors

Abstract: Immune checkpoint inhibitors (ICIs) targeting the PD-1/PD-L1 axis induce sustained clinical responses in a sizable minority of cancer patients. We found that primary resistance to ICIs can be attributed to abnormal gut microbiome composition. Antibiotics inhibited the clinical benefit of ICIs in patients with advanced cancer. Fecal microbiota transplantation (FMT) from cancer patients who responded to ICIs into germ-free or antibiotic-treated mice ameliorated the antitumor effects of PD-1 blockade, whereas FMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

104
3,990
12
37

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,130 publications
(4,436 citation statements)
references
References 35 publications
104
3,990
12
37
Order By: Relevance
“…In responders, there was significantly more bacteria from the species Akkermansia Muniniphila (Verrucomicrobia phylum), the genus Alistipes (Bacteroidetes phylum), and more generally in the phylum Firmicutes. 37 The microbiome composition result of anti-PD-1 Ab responders found in mice by Gajewski and colleagues is different from that of human patients in this publication. As previously discussed, animal studies are inherently different and thus yield results which cannot be easily applied to human studies.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…In responders, there was significantly more bacteria from the species Akkermansia Muniniphila (Verrucomicrobia phylum), the genus Alistipes (Bacteroidetes phylum), and more generally in the phylum Firmicutes. 37 The microbiome composition result of anti-PD-1 Ab responders found in mice by Gajewski and colleagues is different from that of human patients in this publication. As previously discussed, animal studies are inherently different and thus yield results which cannot be easily applied to human studies.…”
contrasting
confidence: 58%
“…35 , 36 A study by Herold and colleagues in December 2017 found systemic immune activation in humanized mice models given anti-CD3 mAb in combination with antibiotics, shown through elevated numbers of effector T-cells and IFN-γ, decreased production of IL-10, and the presence of anti-nuclear antibodies. 35 While there are other investigations demonstrating that gut dysbiosis, or a microbial imbalance or modification in the host gut, may counteract the effects of both immunosuppressive 35 and immunostimulatory drugs, 3 , 23 , 27 , 37 , 38 it may be that microbiota have a more potent or direct interaction with the immune checkpoint drugs rather than the immunomodulatory cells involved per se. All in all, these apparent contradictions reinforce that the function and mechanisms by which commensal bacteria communicate with the immune system are poorly understood and remain a fascinating challenge for prospective researchers.…”
mentioning
confidence: 99%
“…Recently, high-profile studies have demonstrated the role of the microbiome in regulating diverse processes, such as the efficacy of PD-1 treatments for carcinoma/melanoma, the promotion of metastasis in colon cancer, and whole body composition via the circadian clock (Wang et al 2017b;Gopalakrishnan et al 2017;Routy et al 2017;Bullman et al 2017). The exciting potential of understanding the microbiome for translational research was outlined by Miko et al, in CBT (Miko et al 2016).…”
Section: Clinical Influences Of the Microbiomementioning
confidence: 99%
“…For example, in the patients with advanced tumor who received immunotherapy, the use of antibiotics caused poor prognosis. In addition, oral administration of bacteria improved anti-tumor effect [45] . Some immune checkpoints, such as lymphocyte activation gene 3 protein (LAG3) [46] , T-cell immunoglobulin and mucin domain 3 (TIM3) [47] , T-cell immune-receptor with Ig and ITIM domains (TIGIT) [48] are being currently investigated in clinical trials, in order to develop new drugs in the near future.…”
Section: Future Prospect Of Immunotherapymentioning
confidence: 99%